FORMULATION AND EVALUATION OF GASTRORETENTIVE FLOATING BIOADHESIVE TABLETS OF HYDROCHLORTHIAZIDE - B, Ramu; P, Shanmunga Pandiyan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Floating bioadhesive tablets of hydrochlorothiazide were developed to prolong gastric residence time leading to an increase in drug bioavailability where here a combination of floating and bioadhesion mechanism is combined. Methods: Tablets are prepared by direct compression technique using polymers xanthan gum, carbopol 974 P, HPMC K15M, HPMC K100M, magnesium Stearate USP-NF (Avicel PH 102), microcrystalline cellulose Ph 102, Talc, and sodium bicarbonate. Results: Tablets were evaluated for their physical characteristics, namely, hardness, thickness, friability and weight variation, drug content, and floating properties. The best formulation subjected for kinetic treatment, i.e., zero order, first order, peppas, Higuchi, and Hixon-crowel. The R values are 0.9366, 0.9364, 0.9680, 0.9974, and 0.9283, respectively. Conclusion: Optimized formulae F4 containing polymers HPMC K4M and CARBOPOL 974 P showed more bioadhesion with a controlled release over 12 hrs. Therefore, formulation F4 identified as a successful formulation for the development of floating bioadhesive tablets. Â 